2015
DOI: 10.4049/jimmunol.1400643
|View full text |Cite
|
Sign up to set email alerts
|

Extravascular Red Blood Cells and Hemoglobin Promote Tumor Growth and Therapeutic Resistance as Endogenous Danger Signals

Abstract: Hemorrhage is a common clinical manifestation in patients with cancer. Intratumor hemorrhage has been demonstrated to be a poor prognostic factor for cancer patients. In this study, we investigated the role of RBCs and hemoglobin (Hb) in the process of tumor progression and therapeutical response. RBCs and Hb potently promoted tumor cell proliferation and syngenic tumor growth. RBCs and Hb activated the reactive oxygen species–NF-κB pathway in both tumor cells and macrophages. RBCs and Hb also induced chemores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…Complicated microenvironment in tumor results in high heterogeneity of HCC, making the therapeutic effect totally varied. TH in HCC implies tumor microenvironment of red blood cells releasing and platelet aggregation, which could promote tumor growth, invasion, and metastasis partially through the activation of NF-kB pathway [24] , [25] . The inflamed tumor microenvironment is another cause of tumor vessel injury [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Complicated microenvironment in tumor results in high heterogeneity of HCC, making the therapeutic effect totally varied. TH in HCC implies tumor microenvironment of red blood cells releasing and platelet aggregation, which could promote tumor growth, invasion, and metastasis partially through the activation of NF-kB pathway [24] , [25] . The inflamed tumor microenvironment is another cause of tumor vessel injury [26] .…”
Section: Discussionmentioning
confidence: 99%
“…It is not even possible to discard that the expression of CD163 is an immune response to the extravascular hemoglobin content, secondary to necrosis index, eventually increased in tumors from patients receiving the combinatory treatment. Extravascular hemoglobin is a known endogenous danger signal that induces M2-skewed macrophage influx and CD163-macrophage polarization (61, 62). Clinically, CD163 + cell infiltration has been associated to both good (63) and bad (6468) prognosis.…”
Section: Combining Bevacizumab With Immune Modulators To Enhance Antimentioning
confidence: 99%
“…This is because the vast stoichiometric excess of the high affinity heme scavenger protein hemopexin that is present in the plasma (Schaer et al, 2013) would quickly sequester any heme that enters the blood stream from the gut. In addition, heme derivatives released locally from damaged red blood cells within the abnormal neovasculature of cancers (Yin et al, 2015) and atheromas (Balla et al, 2007) seem much more likely to serve as the main sources of heme oxidant compounds in tissues throughout the body. Indeed, it is reported that the interior of advanced atheromatous lesions functions as a pro-oxidant environment in which erythrocytes breakdown and release both heme and iron to promote further lipid oxidation, thereby amplifying endothelial cell cytotoxicity (Balla et al, 1991; Balla et al, 1993; Belcher et al, 1993; Nagy et al, 2010).…”
Section: Existing Theories To Explain Increased Disease Risks Of Rmentioning
confidence: 99%